A comparative study on the first year BSA students' learning style preferences, AY 2010-2011 & AY 2011-2012 - Velasco, Elsie Neri (Animo Repository, 2012)
The study aims to investigate the learning style preferences of first year Bachelor of Science in Accountancy (BSA) students in the College of Business, De La Salle University. Further, the study would like to determine if a significant relationship exists between age and learning style and between gender and learning style. Data were gathered from the 153 regular BSA students enrolled during Academic Year (AY) 2010-2011 and 145 students enrolled during AY 2011-2012. The VARK questionnaire was used to determine their four sensory learning style modalities, namely visual aural, read/write and kinesthetic, Pearson ch-square was used to test the significance of relationship while z-score statistic was utilized to test the proportion of students who are visual, aural, read/write and kinethetic learners. Results show that male and female students have different preferred ways of learning and that no significant relationship exists between age and learning style and similarity between gender and learning style, Analysis of z-square value indicates that visual learners are significantly lesser in AY 2011-2012 than in AY 2010-2011 but of the same proportion for aural, read/write and kinesthetic learners